BIRDs (Brief Potentially Ictal Rhythmic Discharges) watching during EEG monitoring - Yoo, Ji Yeoun (Frontiers in Neurology, 2022)
Brief Potentially Ictal Rhythmic Discharges (BIRDs), initially described in neonates, have been shown to correlate with increased risk of seizures in both critically ill and non-critically ill adults. In critically ill patients, the presence of BIRDs is associated with acute brain injury and worse functional outcome. In non-critically ill adults, BIRDs are seen in patients with epilepsy with greater likelihood of having drug-resistance. The location of BIRDs seems to better predict the seizure onset zone compared to other interictal epileptiform discharges. The definition of BIRDs includes Paroxysmal Fast Activity (PFA) and they have similar clinical significance regardless of the exact cut-off frequencies, and their potential as a biomarker for seizure activity and seizure onset zone have been suggested. In patients with status epilepticus, when seizures resolve, BIRDs also resolve or decrease. Thus, if BIRDs are observed on scalp EEG, longer EEG monitoring is recommended to estimate their seizure burden and to guide treatment. With the recent addition of BIRDs in the critical care EEG terminology, with future investigations, we may soon be able to reach a consensus about the definition of electrographic seizures and better understand their neurophysiology and clinical significance.